PERCEIVED INSUFFICIENT MILK SUPPLY (PIMS) AND THE RISK OF NON-EXCLUSIVE BREASTFEEDING PRACTICES: A SYSTEMATIC REVIEW AND META-ANALYSIS - Siti Nurjanah; Erinda Nur Pratiwi; Erlyn Hapsari; Martina Ekacahyaningtyas (Jurnal Kesehatan Kusuma Husada, 2026)
Background: PIMS, or what is usually called insufficient breast milk supply, is one of the reasons why breastfeeding fails. There are still a few mothers who know about the perception of insufficient breast milk supply and how this has an impact on breastfeeding practices. This study aimed to examine the association between perceived insufficient milk supply (PIMS) and the risk of non-exclusive breastfeeding during the first six months postpartum.Methods: This review was conducted following the PRISMA guidelines to select articles in this study and based on PICO (Population, Intervention, Comparison, Outcome). We searched for relevant articles in five databases, such as PubMed, ScienceDirect, Springer Link, ProQuest, and SAGE journals, from January 2014 to August 2024. Then, they carried out a meta-analysis of the collected data and analyzed the Odds Ratio (OR) using Review Manager 5.3. Overall, 6 studies were appropriate in this review. Results: Six studies were included in the meta-analysis. The forest plot demonstrated a consistent inverse association between perceived insufficient milk supply (PIMS) and exclusive breastfeeding across all included studies. Using a random-effects model, mothers with PIMS had significantly lower odds of exclusive breastfeeding during the first six months postpartum (pooled OR = 0.10; 95% CI: 0.04–0.24; p < 0.00001), indicating a substantially increased risk of non-exclusive breastfeeding. Conclusion: Perceived insufficient milk supply (PIMS) has a relationship with the incidence of failure to provide exclusive breastfeeding.